2016
DOI: 10.1177/0165025415620856
|View full text |Cite
|
Sign up to set email alerts
|

Early family system types predict children’s emotional attention biases at school age

Abstract: Abstract:The family environment shapes children's social information processing and emotion regulation. Yet, the long-term effects of early family systems have rarely been studied. This study investigated how family system types predict children's attentional biases toward facial expressions at the age of 10 years. The participants were 79 children from Cohesive, Disengaged, Enmeshed, and Authoritarian family types based on marital and parental relationship trajectories from pregnancy to the age of 12 months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…These studies have shown that children growing up in rearing environments characterized by chronic violence, maltreatment, and hostility tend to develop overly strong attentional biases to anger cues to adapt their emotional regulation strategies in response to negative interpersonal relationships. More recently, however, scholars have focused their attention on normative developmental contexts and samples (Dodge et al., ; Lindblom et al., ). Although the classroom context plays a prominent role in children's everyday lives, especially in adolescence (Eccles & Roeser, ), its role in influencing students’ attention allocation patterns remains largely unexplored.…”
Section: Attentional Bias For Academic Stressors and School Adjustmentmentioning
confidence: 99%
“…These studies have shown that children growing up in rearing environments characterized by chronic violence, maltreatment, and hostility tend to develop overly strong attentional biases to anger cues to adapt their emotional regulation strategies in response to negative interpersonal relationships. More recently, however, scholars have focused their attention on normative developmental contexts and samples (Dodge et al., ; Lindblom et al., ). Although the classroom context plays a prominent role in children's everyday lives, especially in adolescence (Eccles & Roeser, ), its role in influencing students’ attention allocation patterns remains largely unexplored.…”
Section: Attentional Bias For Academic Stressors and School Adjustmentmentioning
confidence: 99%
“…In general, the family environment influences the cognitive-emotional and psycho-physiological evolution of the child, these influences being felt up to older ages [89]. On the other hand, children's receptivity to spiritual experiences proves their enhanced capacity to develop quality relationships with their own age, but also the willingness to understand the values of their own lives [90], increasing the value of the family environment for the formation of the future adult.…”
Section: Interpersonal Attachment and Nature Contemplation Improvementioning
confidence: 99%
“…On the one hand, documented associations between children's negative internal working models of family relationships and their hostile interpretations of peers in stressful interpersonal contexts provide some indirect support for the schema‐congruent hypothesis (Bascoe, Davies, Sturge‐Apple, & Cummings, ; Granot & Mayseless, ). Moreover, studies have also identified children's exposure to maltreatment, parenting difficulties, and enmeshment in the family as predictors of their heightened attention to negative emotional stimuli (e.g., Gulley, Oppenheimer, & Hankin, ; Lindblom et al., ). Thus, in the context of previous links between adverse family experiences and internal representations, one possibility consistent with the schema‐congruent model is that children's negative family representations increases their negative information processing biases (Crick & Dodge, ).…”
Section: Children's Processing Of Negative Emotions As a Mediator Of mentioning
confidence: 99%
“…On the other hand, research has also generated some piecewise support for the defensive exclusion hypothesis. For example, children's early exposure to family discord and disengagement was associated their diminished processing of negative emotions 9 years later (Lindblom et al., ). Lending preliminary support for the second part of the mediational chain, findings from some cross‐sectional studies have revealed that children's aggression is associated with tendencies to process neutral, rather than hostile, emotional cues (e.g., Horsley et al., ; Schippell, Vasey, Cravens‐Brown, & Bretveld, ).…”
Section: Children's Processing Of Negative Emotions As a Mediator Of mentioning
confidence: 99%
See 1 more Smart Citation